Fair Trade and Islam : A Parallel Journey - Md. Sarwar Uddin; Mohammad Aktaruzzaman Khan (Universitas Trisakti, 2014)
Fair trade is an organized social movement through wider network of producers, importers, retailers and consumers who are thinking globally to promote trading partnership of products, based on mutually agreed upon condition, accountability & transparency, social justice and equity for livelihood sustainability and economic development by creating fairer and better conditions of trade. It secures the rights of marginalized producers and workers especially, in the underdeveloped and developing countries in order to help them move from a position of vulnerability to security and economic selfsufficiency, supporting environmentally feasible, socially acceptable and economically viable production and distribution of Fair Trade labeled and unlabeled goods. Again Islam urges on establishing Adl, Ehsan and eleminating Julum and Haram from trade and business to establish peace and prosperity in the society. This paper attempts to draw a line of linkage between fair trade and Islam. It also has the endeavour to unveil that the guidelines in the Holy Quran and the Sunnah are the roots and indications of Fair trade. Moreover, the principles of fair trade which are focused now have pronounced in Islam long ago. Archive method of study has been followed to conduct the research through pursuing Quran, Sunnah, different books, journals and web materials. A substantial number of researchers have focused issues related to business ethics and Islam but the issue of Fair trade and Islam has got very little attention by the early researchers. This research gap has created proclivity in the present researchers to conduct the study. This paper will be a valuable document in enriching the literature in this field and will create dimensions for further research. Key words: Fair trade, Islam